Pelvic pain and early IUD discontinuation: a prospective cohort study - Gerber, Sharon R.; Nattell, Noah; Doty, Nora; Liu, Xiaoyu; Overbey, Jessica R.; Masch, Rachel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of the study is to assess if pelvic pain is a risk factor for intrauterine device (IUD) discontinuation within one year of placement. Methods: This is a prospective cohort study of women who had IUDs inserted at a family planning office for the primary intent of contraception. Baseline pelvic pain characteristics were assessed using a validated pelvic pain questionnaire. Women were contacted at 1 year to assess IUD continuation. Results: From February 1, 2014 to August 11, 2015 authors enrolled a sample of 179 women. Of the 179 enrolled,163 participants completed the questionnaire, 98 reported a history of baseline pelvic pain and 65 reported no history of baseline pelvic pain. 20 participants were lost to follow-up. 86 women in the pelvic pain and 57 in the no pelvic pain group were included in the final analysis. Discontinuation rates at one year follow up were 25.6% (22) and 35.1% (20) respectively. There was no significant difference in those with and without pelvic pain discontinuing IUDs at one year (p = 0.22). Conclusions: Baseline generalized pelvic pain may not be a risk factor for IUD discontinuation within one year of placement.